The age of revolution Europe 1789-1848 - Hobsbawm, Eric (London Abacus books, 1977)
Age Of Revolution 1789-1848 offers an engaging, educational look at the sixty years when the French Revolution and the Industrial Revolution together reshaped European life. This accessible history book is perfect for students, history enthusiasts, and curious readers who want a clear, thought-provoking account of how revolutions and industry transformed the world.